2008
DOI: 10.1007/s10764-007-9219-4
|View full text |Cite
|
Sign up to set email alerts
|

Ranging Behavior and Possible Correlates of Pair-Living in Southeastern Avahis (Madagascar)

Abstract: Researchers have proposed several hypotheses to explain pair-living in primates. In particular, when males are not involved in direct parental care, pairliving may be related to female dispersal, infanticide prevention, or male mate/ resource defense. We aimed to evaluate, through a better understanding of the ranging patterns of avahis, which hypotheses may best account for pair-living in these nocturnal lemurs. We collected focal observations over 26 nights, JuneSeptember 2004, in a littoral forest (Sainte L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Physical contact only occurs during the mating season when the male, who defends the range against other males (but not females), maintains proximity [Hilgartner et al, 2012]. Some "dispersed pair-living" species are considered monogamous (e.g., redtailed sportive lemur, L. ruficaudatus; [Hilgartner et al, 2008]; Eastern wooly lemur, Avahi laniger; [Norscia & Borgognini-Tarli, 2008]; Milne-Edwards' sportive lemur, Lepilemur edwardsi; [Thalmann 2001]), though genetic analyses to confirm monogamy have only been reported in red-tailed sportive lemurs (see [Hilgartner et al, 2008[Hilgartner et al, ,2012). In other dispersed pair-living species, extra-pair paternity can be quite high (e.g., P. furcifer's rate of extra-pair paternity is 0.75, n ¼ 4 [Sch€ ulke et al, 2004]).…”
Section: Pair-living Pair-bonding and Monogamy In Lemuroideamentioning
confidence: 99%
See 1 more Smart Citation
“…Physical contact only occurs during the mating season when the male, who defends the range against other males (but not females), maintains proximity [Hilgartner et al, 2012]. Some "dispersed pair-living" species are considered monogamous (e.g., redtailed sportive lemur, L. ruficaudatus; [Hilgartner et al, 2008]; Eastern wooly lemur, Avahi laniger; [Norscia & Borgognini-Tarli, 2008]; Milne-Edwards' sportive lemur, Lepilemur edwardsi; [Thalmann 2001]), though genetic analyses to confirm monogamy have only been reported in red-tailed sportive lemurs (see [Hilgartner et al, 2008[Hilgartner et al, ,2012). In other dispersed pair-living species, extra-pair paternity can be quite high (e.g., P. furcifer's rate of extra-pair paternity is 0.75, n ¼ 4 [Sch€ ulke et al, 2004]).…”
Section: Pair-living Pair-bonding and Monogamy In Lemuroideamentioning
confidence: 99%
“…We define pair-living as a demographic structure or social organization, in which two adults of opposite sex live together within a home range with their non-reproducing offspring [sensu Norscia & Borgognini-Tarli, 2008]. Fuentes [1998] referred to this category as a "two-adult group."…”
Section: Introductionmentioning
confidence: 99%
“…Avahis are particularly intriguing in this context because their body mass is at the lower limits for primate folivores (750-1400 g: Kay 1984;Lehman 2007), they are nocturnal (Norscia and Borgognini-Tarli 2008) and thus active at a time when low ambient temperature possibly increases metabolic requirements to remain normothermal (Willmer et al 2000), and their locomotion is energetically expensive (vertical leaping; Warren and Crompton 1997). Like all indriids, Avahi spp.…”
Section: Malagasy Folivoresmentioning
confidence: 99%
“…Most include other home range estimators besides MCP (e.g. Grueter et al 2008, Norscia & Borgognini-Tarli 2008, Neri-Arboleda 2002, NewtonFisher 2003.…”
Section: Home Range Modelsmentioning
confidence: 99%
“…In primatology, researchers have also begun to incorporate kernel methods for range estimates, mainly as an addition to MCP or grid cell methods (e.g. Neri-Arboleda et al 2002, NewtonFisher 2003, Fashing et al 2007, Norscia & Borgognini-Tarli 2008. In their review of home range studies in wildlife biology, Laver & Kelly (2008) found 60% of studies reporting ranges with kernel methods, with 21% of studies solely relying on kernel methods.…”
Section: Home Range Modelsmentioning
confidence: 99%